Penerapan Media Pembelajaran Paludarium untuk Meningkatkan Minat Belajar Siswa pada Pembelajaran Biologi - Fu’ad Hasan; Haning Hasbiyati; Imam Bukhori Muslim (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The implementation of learning at Ma Ma'arif Ambulu experienced problems in the form of low student interest in learning. This incident was shown from the results of student learning in the previous semester with only 50% of students getting a KKM score of 70. The cause of the lack of delivery of learning in class was due to the lack of learning media, when delivering learning in class. This resulted in students being less interested and less active in seeking more information related to the material being studied. The study was conducted using classroom action research with a data analysis method in the form of a questionnaire to measure student interest in learning. Based on the analysis of data from cycle I, it was found that student interest in learning was in the low category of 56.75% and cycle II, it was found that student interest in learning was 83.71% which was included in the high ability category. The conclusion obtained is that learning using the Paludarium learning media can increase the interest in learning of class X IPA I MA Ma'arif Ambulu students in the 2022/2023 academic year totaling 28 students in the Ecosystem material.